Effect of Impact Speed and Position of Pedestrian on Lower Extremity Injuries Caused by a Pickup Truck in Traffic Accidents - Anh, Ly Hung; Toan, Vuong Minh (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Pedestrians often suffer severe injuries in road traffic accidents. Therefore, pedestrian safety and, more precisely, analysis of injuries of the knee joint and lower limb bones were the focus of this research. A Vietnamese-sized human body model (HBM), named V-THUMS, scaled from the Total Human Model for Safety (THUMS) representing a walking pedestrian, was utilized in a numerical simulation. A pickup truck model was used to simulate pedestrian collisions with impact speeds from 20 km/h to 50 km/h. To reduce the computational time, the pickup truck model was simplified. In addition, the collision angle was varied from 0o, 30o, 60o, 90o, -30o, -60o to -90o to explore the effect of angle position on the injury mechanisms of the leg. The results illustrate that in some cases at low speeds there is a relationship between bone fracture and ligament rupture that does not exist at high speeds. The femur is very difficult to fracture because the bone is very hard and thick. It was found that at 20 km/h impact speed, the lower limbs are unharmed.